Korelasi Kepadatan Konidium Dan Kelembapan Udara Dengan Intensitas Serangan Cercospora Sp. Pada Tanaman Edamame Di Areal Tanaman Kelapa Sawit Belum Menghasilkan - Devi Asriani Br Simanihuruk; Guntoro; Henry Budi Hasibuan (Lembaga Teewan Journal Solutions, 2026)
Leaf spot disease caused by Cercospora sp. is a major constraint in edamame (Glycine max L.) cultivation, reducing both crop quality and yield. This study aimed to analyze the relationship between conidia density and air humidity with disease severity and to develop a predictive statistical model for disease management. The research was conducted at the ITSI experimental field, Deli Serdang, North Sumatra, from March to June 2026 using a descriptive-correlational survey method involving 45 observation periods across five 5 × 5 m plots. Data were analyzed using Pearson correlation and multiple linear regression. The results showed that air humidity had a very strong and significant positive correlation with disease severity (r = 0.910; p < 0.001), whereas conidia density exhibited a weak and non-significant correlation (r = 0.189; p = 0.213). The resulting regression model, Ŷ = −286.310 + 4.040X₂ + 0.188X₁ (R² = 0.831), explained 83.1% of the variation in disease severity. Air humidity was identified as the dominant predictor, while conidia density had no significant effect. In conclusion, environmental humidity management is the primary factor in controlling Cercospora sp. in productive edamame fields. The novelty of this study lies in the development of a predictive model integrating conidia density and air humidity as the basis for an early warning system for disease management.